Canadian Labour in Crisis: Reinventing the Workers' Movement - Camfield, David (Fernwood Publishing, 2011)
Does Canada have a working-class movement? Though most of us think of ourselves as middle class, most of us are, in fact, part of the working class: we work for wages and are not managers. Although many of us are members of unions - the most significant organizations of the working-class movement in Canada - most people do not understand themselves to be part of this movement. Is the working-class movement a relic of the twentieth-century factory worker, no longer relevant to workers in the twenty-first century? David Camfield argues that, despite its real deficiencies, the movement is as important today as it was a hundred years ago. Drawing on the ideas of union and community activists as well as academic research, David Camfield offers an analysis of the contemporary Canadian working-class movement and how it came to be in its current state. he argues that re-energizing the movement in its current form is not enough - it needs to be reinvented to face the challenges of contemporary capitalism. Considering potential ways forward, Camfield asserts that reforming unions from below and building new workers' organizations offer the best possibilities for effecting real change within the movement. –Publisher's description
Keywords: Canada; Labor Unions; Labor movement; Political activity; Social conditions; Working class